Recurrent laryngeal nerve management in transoral endoscopic thyroidectomy. (September 2020) - Zhang, Daqi; Sun, Hui; Tufano, Ralph; Caruso, Ettore; Dionigi, Gianlorenzo; Kim, Hoon Yub
Highlights: The incidence of temporary and permanent RLN dysfunction were 5.9% and 0.5%. A disrupted point (type 1 injury) could be identified in 7/12 nerves; 5 nerve injuries were classified as global. 3 lesions occurred at RLN laryngeal entry point, during nerve identification. Four type 1 injuries were at distal 1 cm of the RLN course, during earliest nerve dissection (1 injury). Mechanisms of injury were thermal (58%) during energy-based device use. Two traction injuries occurred during earliest nerve dissection. Abstract: Introduction: The mechanism of recurrent laryngeal nerve (RLN) injury was investigated during a TransOral Endoscopic Thyroidectomy Vestibular Approach (TOETVA). Methods: The function of 185 nerves at risk (NAR) was recorded with intermitted intraoperative neural monitoring (I-IONM). The RLN electromyography (EMG) was delineated during: (a) a pre-dissection vagal nerve stimulation; (b) a RLN stimulation at initial visualization; (c) at nerve dissection; and (d) at the final verification of the entire RLN route. The location, genesis, segmental or diffuse and the outcomes of RLN injuries were catalogued. Results: Twelve nerves (6.4%) lost the EMG signal and the incidences of temporary and permanent RLN dysfunction were 5.9% and 0.5%. A disrupted point (type 1 injury) could be identified in 7/12 nerves (58%). Five (42%) nerve injuries were classified as global (type 2). Of the seven type 1 injuries, 3 lesions occurred at the RLN laryngeal entry point during the nerve identification. Four type 1 injuries were at the distal 1 cm of the RLN course and during the early nerve dissection. No proximal (>2 cm) injuries occurred. The mechanisms of the injuries were thermal (58%) during the energy-based device use at the ligament of Berry dissection or at the dividing small branches of the inferior thyroid artery. Two (16%) traction injuries occurred during the early nerve dissection. In 2 cases we could not elucidate the mechanism of RLN injury (16%) and 1 injury (8%) was caused by the connective tissue constricting band of. The thermal RLN lesions had longer recovery times. Conclusions: The RLN palsy occurs in TOETVA, even when combined with an endoscopic magnification, IONM, early nerve identification, cranial to caudal dissection and top-down view. The thermal RLN injury was the most frequent cause and all injuries occurred at the distal RLN course.